Remarks on the Impact of Science and Technology Progress on International Relations in Digital Era - A. V. Biryukov (Международная аналитика, 2015)
The article investigates the problem of Science and Technology impact on International Relations. Special attention was drawn to International Science and Technology Relations in Digital Era. They are developing within the context of Global Information Revolution and transition to Multipolar World. In the prospective part the article deals with transformation of International Science and Technology Relations and establishment of Global Technology Alliance. The latter could include creation of Global Technology Fund, renovation of Global Technology Transfer and broadening of Global Cloud Technology Resource.